TAFSIR KONTEKSTUAL ATAS MODERASI DALAM AL-QUR - Ghozali, Mahbub; Rizal, Derry Ahmad (Jurnal Studi Agama dan Masyarakat, 2021)
This study focused on the meaning of the word moderate in the Qur'an contextually with reference to the QS. [2]: 143 and QS. [5]: 66. The idea of